POTRET KEKUATAN MULTIKULTURALISME DALAM INSTITUSI POLITIK - Fathullah Syahrul (Journal Publicuho, 2020)
The study of the relations of cultural elements, namely multiculturalism and politics, is still relatively developed. Because, the study is vulnerable to conflict, especially when faced with the word majority and minority in the realm of political institutions. As a country with a pluralistic background inhabited by various ethnicities, racial religions and Indonesian culture, certainly requires an in-depth study of the fulfilment of minority rights in the political institutions. This paper is a simple theoretical study of a combination of multiculturalism and institutionalism approaches to explain the prospects of minority involvement in formulating public policies and political institutions that must be present in accommodating the political rights of minority groups. The conclusions in this article are, the power of multiculturalism in political institutions is as follows: (1) multicultural countries must be able to provide lessons for the whole world about the meaning of diversity; (2) the institution becomes a bridge in absorbing all the aspirations of the people and carrying out the law and applying the law indiscriminately; (3) multiculturalism is actually not enough to discuss minority rights in political institutions but conflicts with grassroots sources; (4) the strength of multiculturalism in political institutions is how this study works in maintaining the harmony of the nation and state.